The relationship between portuguese adolescent perception of parental styles, social support, and school behaviour - Silva, José Maria Castro (2012)
The present article describes preliminary results of a study that aims to analyse the relationship among Portuguese adolescent perception of parental styles, social support received from family and peers and their school behaviour. Participants were 537 adolescents aged between 14 and 16. The “Parental Author- ity Questionnaire”, the “Perceived Social Support-Friends Scale” and “Perceived Social Support-Family Scale” were used to measure adolescent perceptions. Overall, Portuguese adolescents perceive their par-ents as using predominantly a democratic parental style. Associations between school behaviour and pa-rental styles show that “well-behaved” adolescents perceive their parents as less permissive. On the other hand, adolescents who misbehave perceive their parents as more permissive and authoritarian. As regards the relationship between perceived school behaviour and social support, adolescents recognise receiving greater support from peers than from family, and adolescents who “often behave badly” are those who re-fer to receiving less social support, either from the family or peers.